Les Champs de la Sculpture. - Tiberi, Jean (Tokyo : Museum of Contemporary Art, 1996)
Agam, Yaacov ; Arman ; Arp, Hans (Jean) ; Bourdelle, Antoine ; Bourgeois, Louise ; Bury, Pol ; Calder, Alexander ; Caro, Anthony ; César ; Chillida, Eduardo ; Clave, Antoni ; Dubuffet, Jean ; Etienne-Martin ; Gargallo, Pablo ; Giacometti, Alberto ; Gilioli, Emile ; González, Julio ; Hepworth, Barbara ; Leger, Fernand ; Les Lalanne ; Maillol, Aristide ; Miro, Joan ; Pan, Marta ; Richier, Germaine ; Rodin, Auguste ; de Saint Phalle, Niki ; Schoffer, Nicolas ; Soto, Jesus Rafael ; Takis ; Zadkine, Ossip
Les Champs de la Sculpture, Museum of Contemporary Art, Tokyo, 1996.09.28 - 11.24
French-Japanese
kunstcatalogus